Does Expert Advice Improve Educational Choice? - Lex Borghans; Bart H.H. Golsteyn; Anders Stenberg (Institute for the Study of Labor (IZA), 2013)
This paper reports evidence that an individual meeting with a study counselor at high school significantly improves the quality of choice of tertiary educational field, as self-assessed 18 months after graduation from college. The results are strongest among males and those with low educated parents. To address endogeneity, we explore the variation in study counseling practices between schools. Tentative analyses also indicate that counselors reduce students' uncertainty about their own individual preferences at least to the same extent as uncertainty about objective measures such as employment prospects.
Keywords: I2; J24; J31; 330; uncertainty; human capital; educational choice; study counseling